O poezji współczesnego poety z perspektywy baroku = On a contemporary poet's output from the Baroque perspective - Linkner, Tadeusz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Stanisław Gostkowski, a contemporary poet, author of seven volumes, died in 2000. He did not belong to the New Wave and New Privacy. His literary patron was Tymoteusz Karpowicz. I am writing about the first volume, "Don't bury me alive", and the fourth one, titled "Death has a sweet smell". Gostkowski wrote about death, nevertheless just for life. He often emphasises vanitas in his poetry. Here is an interpretation of his output from the Baroque perspective.
Keywords: Śmierć; vanitas; oksymoron; koncept; Gostkowski, Stanisław (1948-2000); death; oxymoron; concept